“It is not what I planned for my life”. Occupations of live-in domestic workers/“Não foi isso que planejei para minha vida”. Ocupações de empregadas domésticas que moram no local de trabalho - Dos Santos, Vagner; Oliveira Rodrigues, Izabella; Galvaan, Roshan (Cadernos Brasileiros de Terapia Ocupacional, 2019)
Introduction: In Brazil, nearly 20% of women in the country are domestic workers. Domestic work has a restrictive nature that can lead to occupational deprivation and occupational marginalization. This may be the case of live-in domestic workers in Brazil. Objective: Our research question was: What are Brazilian domestic workers’ experiences in participating in their occupations in everyday life? Method: A qualitative phenomenological was carried out and thought purposive sampling 5 participants were selected in the Plano Piloto region, Brasilia, DF, Brazil. Data was collected through face-face interviews and analyzed using Systematic Text Condensation. Results: The data analysis yielded one theme and two categories. The theme, Grappling with being a domestic worker, described the domestic workers ongoing confrontations and tensions experienced in their daily lives. This experience of wresting with the influence of being a domestic worker was constituted through two categories, namely a sense of ‘Belonging to the labor role’ and ‘Exceptionalism: a employers’ negotiation tactic’. Conclusion: Our work contributes to a critical perspective of occupation. We focus on how historical, social and political factors contribute to creating oppressive environments that influences domestic workers as people who are part of a marginalized group. This occurs in the way that their occupations are constructed in their doing in every-day life.